A network pharmacology approach with experimental validation to discover protective mechanism of poly herbal extract on diabetes mellitus - Singh A.K.; Kumar P.; Mishra S.K.; Tiwari K.; Singh A.K.; Pandey A.K.; Shati A.A.; Alfaifi M.Y.; Elbehairi S.I.; Sayyed R.Z. (My University, 2025)
Objective: Polyherbal extracts (PHE) contain six traditional medicinal plants, and the efficacy of the medicinal plants used in the preparation of this PHE has been confirmed for the treatment of diseases like diabetes mellitus (DM). The aim of this study was to evaluate the efficacy and therapeutic mechanism of PHE through a network pharmacology approach to reveal the protective mechanism of Alpha-Tocospiro A (ATA) present in PHE on DM with experimental validation. Methods: In this study, Lipinski's rule (Swiss ADME) and drug-likeness score (MolSoft's) web pages were used to confirm the drug-likeness of identified constituents in PHE. Swiss Target Prediction (STP) genes were found for ATA-related genes. The DisGeNet database was used to screen genes associated with DM. String created a network diagram of the interactions between the ATA and DM genes. Top-scoring genes from the string network through CytoNCA plugged into Cytoscape 3.8.2 were selected as hub genes. In addition, the ShinyGO database is used to predict GO and KEGG pathway enrichment analyses. Results: A total of 675 and 105 therapeutic genes (STP) were associated with all bioactive compounds and ATA in the PHE screen, respectively. Additionally, a maximum of 2,803 DM-related genes (DisGeNet) were observed. Further, in the analysis, 331, 57 potential (intersecting) genes were identified in the correlation between the target genes of all compounds and ATA, respectively, of PHE and the target genes of DM. The identified hub gene “TNF” for both ATA and PHE was found to be precisely strengthened in 49 pathways, along with 14 signaling pathways out of more than 100 enriched KEGG pathways. This study predicted that ATA activates PI3K/Akt and MAPK pathways enriched with TNF by phosphorylating the insulin receptor (IR) β-subunit. The anti-diabetic activity of PHE was found to be good and primarily confirmed by in vitro α-glucosidase enzyme inhibition activity. Conclusion: The anti-diabetic activity of PHE was found to be effective and was confirmed by the enzyme inhibition activity in the primary study. This study predicted that ATA is a novel drug molecule in PHE that has a targeted mechanism of action and therapeutic effect on DM. © 2024 The Author(s)